Determinantes da contribuição previdenciária e da constituição jurídica dos autonômos no Nordeste - Nascimento, Otemberges Borges do (2010)
This study aims to investigate the determinants factors of both the juridical formalization and the social security contributions in the northeast of the autonomous. It was used for this purpose, a Modelo Logit Multivariado de Probabilidade of legalization of the business and contribution to foresight, based on data from the IBGE ECINF 2003. A key question to answer is if the levels of income (reservation prices) required for these forms of legalization of micro-business are the same. The results showed that the effect of the gross revenue of the autonomous is different for these two decisions (record and contribution to foresight). While the initial level of income to which the trend of legal formalization is 1,5 to 2 minimum wages, to the social security contribution it is situated in the range of between 2,5 to 3 minimum wages. Other important factors outstanding to the decision of contribution and formalization refer to the presence of steady clientele, counter and obtain loans. These variables were statistically significant and positive, suggesting that policies of public guarantees, technical support and microcredit can also improve the formalization of autonomous. About the economic effects (marginal effects), were low, indicating that the attraction of autonomous to formalization has to overcome the incentives only accounting costs. A more rigorous supervision and other bureaucratic facilities can complement policy of tax relief in the microenterprises.